Coexistence of negative and positive electrocaloric effect in lead-free 0.9(K0.5Na0.5)NbO3 - 0.1SrTiO3 nanocrystalline ceramics. (15th January 2018) - Gupta, Arti; Kumar, Raju; Singh, Satyendra
Abstract: The coexistence of negative and positive electrocaloric effect have been experimentally demonstrated in lead-free 0.9(K0.5 Na0.5 )NbO3 - 0.1SrTiO3 nanocrystalline ceramics using an indirect thermodynamic method. The electrocaloric response of − 0.85 K at 276 K and 0.43 K at 330 K were calculated at 40 kV/cm. The corresponding electrocaloric coefficient were estimated to be − 0.24 × 10 − 7 K·mV − 1 and 0.7 × 10 − 7 K·mV − 1 at 273 K and 333 K, respectively. A large electrical storage energy density 1.46 J/cm 3 were achieved. The results indicate that materials possess a huge potential for electrocaloric refrigeration as a micro-cooler and energy storage capacity for electronic devices. Graphical abstract: Image 1